25m +22n = -19 ;22m+25n = -28
Answers
Answer:
answer is given above hope this answer will help you
![](https://hi-static.z-dn.net/files/d63/86c611b47b2783f9060e9d9f17ce4fe6.jpg)
Answer:
m = 1
n = -2
Solution:
Given equations are :
25m +22n = -19 -------(1)
22m + 25n = -28 -------(2)
Adding eq-(1) and (2) , we get ;
=> 25m + 22n + 22m + 25n = -19 + (-28)
=> (25m + 22m) + (22n + 25n) = -19 - 28
=> 47m + 47n = -47
=> 47(m + n) = -47
=> m + n = -47/47
=> m + n = -1 -------(3)
Now,
Consider eq-(1)
=> 25m +22n = -19
=> (3m + 22m) + 22n = -19
(25m = 3m + 22m)
=> 3m + 22m + 22n = -19
=> 3m + 22(m + n) = -19
=> 3m + 22×(-1) = -19
{using eq-(3) , m + n = -1}
=> 3m - 22 = -19
=> 3m = 22 - 19
=> 3m = 3
=> m = 3/3
=> m = 1
Now,
Putting m = 1 in eq-(3) , we have ;
=> m + n = -1
=> 1 + n = -1
=> n = -1-1
=> n = -2
Hence,
The required values of m and n are 1 and (-2) respectively.